Ni/N co-doped P25 TiO2 photoelectrodes for efficient Dye-Sensitized Solar Cells - Rajaramanan, T.; Kumara, G.R.A.; Velauthapillai, D.; Ravirajan, P.; Senthilnanthanan, M. (University of Jaffna, 2021)
This study focuses, synthesising and characterising Ni/N co-doped P25–TiO2 nanostructure electrodes for photovoltaic application. The X-ray diffraction (XRD) patterns confirm the presence of major anatase and minor rutile phases of TiO2 for un-doped, doped and co-doped nanoparticles. The UV–Visible spectra of un-doped, Ni doped, N-doped and Ni/N co-doped nanoparticles reveal gradual red shift in light absorption and reduction in TiO2 bandgap. Enhanced light absorption observed for dye-coated Ni/N co-doped TiO2 electrode relative to the doped and un-doped electrode may be attributed to the increased surface area for dye adsorption/dye loading capacity due to synergistic effect of Ni and N doping. The improved surface roughness of Ni/N co-doped TiO2 electrode, confirmed by AFM, leads to high dye adsorption. The photovoltaic performance of the fabricated DSSCs was examined under simulated irradiation intensity of 100 mWcm− 2 with AM 1.5 filter. The Ni/N co doped device exhibited 35% higher than that of the control device (un-doped TiO2 based DSSC). The improvement in the PCE of the co-doped device is predominantly due to the increase in short circuit current density (JSC) as a result of higher light absorption ability and reduced charge transport resistance of the co-doped electrode.
Keywords: Dye-sensitized solar cells; Co-doped TiO2; P25–TiO2; Nitrogen (N); Nickel (Ni)